2023
DOI: 10.1186/s12916-023-02907-6
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and all-cause and cause-specific mortality among US adults: prospective cohort study

Abstract: Background Previous studies have shown inconsistent findings regarding the association of light to moderate alcohol consumption with cause-specific mortality. Therefore, this study sought to examine the prospective association of alcohol consumption with all-cause and cause-specific mortality in the US population. Methods This was a population-based cohort study of adults aged 18 years or older in the National Health Interview Survey (1997 to 2014)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Continued heavy alcohol use can cause substantial morbidity and mortality from all causes, cancer, and accidents [ 36 ]. Light and moderate alcohol consumption have been inversely associated with mortality from all causes, cardiovascular disease, chronic lower respiratory tract diseases, Alzheimer’s disease, and influenza and pneumonia [ 37 ]. Clarifying the relationship between alcohol status and higher daily liquor consumption and all-cause mortality can help healthcare professionals better advise their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Continued heavy alcohol use can cause substantial morbidity and mortality from all causes, cancer, and accidents [ 36 ]. Light and moderate alcohol consumption have been inversely associated with mortality from all causes, cardiovascular disease, chronic lower respiratory tract diseases, Alzheimer’s disease, and influenza and pneumonia [ 37 ]. Clarifying the relationship between alcohol status and higher daily liquor consumption and all-cause mortality can help healthcare professionals better advise their patients.…”
Section: Discussionmentioning
confidence: 99%
“…35 It is also worth emphasizing that there is a reason why the recommendations indicate that the consumed doses of alcohol should not be accumulated. In a prospective study by Tian et al, 36 including 918 529 participants followed for 12.65 years, it was found that binge drinking for 1 or more days a week was associated with a higher risk of mortality from all causes (HR, 1.15; 95% CI, 1.09-1.22), cancer (HR, 1.22; 95% CI, 1.1-1.35), and accidents (unintentional injuries) (HR, 1.39; 95% CI, 1.11-1. 74).…”
Section: European Society Of Hypertension (2023)mentioning
confidence: 99%
“…Current epidemiologic data on alcohol consumption Global epidemiology In 2016, approximately 32.5% (with a 95% uncertainty interval [UI], 30-35.2) of the world's population were reported as current drinkers. Specifically, 25% of women (95% UI, [23][24][25][26][27] and 39% of men (95% UI, [36][37][38][39][40][41][42][43] were identified as such. These percentages equal to a total of 2.4 billion people (95% UI, 2.2-2.6) who were current drinkers, comprising 1.5 billion current drinkers among men (95% UI, 1.4-1.6) and 0.9 billion among women (95% UI, 0.8-1).…”
mentioning
confidence: 99%
“…A J-shaped relationship has been observed between alcohol intake and the risk of CVD, whereby lower and moderate alcohol intake is associated with a decreased risk of CVD incidence and mortality. 118 However, heavy drinking significantly increases the incidence and mortality of CVD. 119 Recent investigations have unveiled distinctive characteristics in the gut microbiota of individuals with long-term alcohol consumption.…”
Section: Middle Agedmentioning
confidence: 99%